Canadian Laboratory Standards for Sexually Transmitted Infections: Best Practice Guidelines. Issue 1 (2005) - Chernesky, Max A; Patrick, David
Abstract : Sexually transmitted infections (STI) continue to spread, and show no international boundaries. Diseases such as gonorrhea and syphilis, which we thought were under control in Canadian populations, have increased in incidence. Sexually transmitted or associated syndromes such as cervicitis, enteric infections, epididymitis, genital ulcers, sexually related hepatitis, ophthalmia neonatorum, pelvic inflammatory disease, prostatitis and vulvovaginitis present a challenge for the physician to identify the microbial cause, treat the patient and manage contacts. During the past 10 years, new technologies developed for the diagnosis of STIs have provided a clearer understanding of the real accuracy of traditional tests for the diagnosis of infections caused by Chlamydia trachomatis, Neisseria gonorrhoeae, Treponema pallidum, herpes simplex viruses, hepatitis B virus, human papillomaviruses, HIV, Haemophilus ducreyi, Trichomonas vaginalis and mycoplasmas. This has presented a major challenge to the diagnostic laboratory, namely, selecting the most sensitive and specific test matched with the most appropriate specimens to provide meaningful and timely results to facilitate optimal patient care.